Fiscal Deficits and Inflation - Catao, Luis (IMF Working Papers; Working Paper ;, 2003)
Macroeconomic theory postulates that fiscal deficits cause inflation. Yet empirical research has had limited success in uncovering this relationship. This paper reexamines the issue in light of broader data and a new modeling approach that incorporates two key features of the theory. Unlike previous studies, we model inflation as nonlinearly related to fiscal deficits through the inflation tax base and estimate this relationship as intrinsically dynamic, using panel techniques that explicitly distinguish between short- and long-run effects of fiscal deficits. Results spanning 107 countries over 1960-2001 show a strong positive association between deficits and inflation among high-inflation and developing country groups, but not among low-inflation advanced economies.